ANALISIS GAYA KOGNITIF DAN KEMAMPUAN SPASIAL PESERTA DIDIK DALAM KEMAMPUAN PEMECAHAN MASALAH PADA MATERI TRIGONOMETRI - Ernaningsih, Zeny (Media Pendidikan Matematika, 2020)
This study aims to describe students’ cognitive styles and spatial abilities in problem solving on geometry so that educators can determine the appropriate learning methods, models and instruments for their students. This research is a qualitative descriptive study. Data were collected from 25 students of class X MIPA 2 SMA Pangudi Luhur Yogyakarta through observation of the learning process, analysis of student test results in terms of imagination, conceptualization and problem solving and interviews to find out more about the stages of problem solving. From the research conducted, it was found that less than 50% of students were able to meet 3 indicators of good spatial ability so that assistance was needed in (1) turning the problem into a 2-dimensional image, (2) determining the concept used based on the information on the problem presented, (3) determine the solving strategy of the concepts used to solve the problem. For cognitive style, students of class X MIPA 2 tend to have a reflective and Field Dependent cognitive style where out of 25 students, 16 people have a reflective cognitive style, that is, students think a lot before working on the questions even though there are still some who have not found the right solution because of inaccuracy and lack of time management . In addition, it is also known that there is a relationship between spatial abilities, cognitive styles and problem solving abilities, where students with reflective cognitive styles tend to have good spatial abilities in problem solving abilities